2020
DOI: 10.1007/s11239-020-02179-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness and safety of direct oral anticoagulants compared to warfarin in morbidly obese patients with acute venous thromboembolism: systematic review and a meta-analysis

Abstract: Direct oral anticoagulant (DOAC) agents are becoming the anticoagulation strategy of choice. However, their use in the treatment of acute venous thromboembolism (VTE) in morbidly obese patients (bodyweight of > 120 kg or BMI > 40 kg/ m 2) guarded. This is due to the scarce data supporting their use in this population. As a result, the International Society on Thrombosis and Haemostasis recommended against their use in this cohort of patients. New data emerged supporting the use of DOACs in these patients. Henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 45 publications
7
43
0
Order By: Relevance
“…Clinical outcomes associated with DOACs in obese patients remain to be elucidated in RCTs. To date, four published systematic reviews and meta‐analyses provide insight into this population 48‐50 . Most studies in these reviews were retrospective observational analyses of patients with body mass index (BMI) >40 kg/m 2 or weight >120 kg and included rivaroxaban or apixaban 48 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Clinical outcomes associated with DOACs in obese patients remain to be elucidated in RCTs. To date, four published systematic reviews and meta‐analyses provide insight into this population 48‐50 . Most studies in these reviews were retrospective observational analyses of patients with body mass index (BMI) >40 kg/m 2 or weight >120 kg and included rivaroxaban or apixaban 48 .…”
Section: Resultsmentioning
confidence: 99%
“…Most studies in these reviews were retrospective observational analyses of patients with body mass index (BMI) >40 kg/m 2 or weight >120 kg and included rivaroxaban or apixaban 48 . Overall, retrospective cohorts of AF and VTE identified no significant differences between specific DOACs and warfarin for thromboembolism or major bleeding events 48,49,51 . One post hoc analysis of the ARISTOTLE trial found that, compared to warfarin, apixaban was associated with a lower rate of SSE in patients with BMI 35–40 kg/m 2 (HR 0.31, 95% CI 0.13–0.74) and lower rates of major bleeding in BMI 25–30 kg/m 2 (HR 0.73, 95% CI 0.57–0.92).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis of these five observational studies that specifically evaluated patients with VTE and a BMI greater than 40 kg/m 2 or a weight greater than 120 kg (n ¼ 6585) has been published. 93 There was no difference in the primary efficacy endpoint of recurrent VTE (odds ratio [OR]: 1.07, 95% CI: 0.93-1.23) or in the primary safety endpoint of major bleeding (OR: 0.80, 95% CI: 0.54-1.17). It should be noted that 88% of the patients in the meta-analysis come from the study by Spyropoulos and colleagues, and the majority of the DOAC use was rivaroxaban followed by apixaban.…”
Section: Data From Observational Studiesmentioning
confidence: 94%